Transplantation of cardiac allografts with left ventricular hypertrophy 1.5 cm and more - V. N. Poptsov; E. A. Spirina; S. Yu. Ustin; S. A. Masutin; A. A. Dogonacheva; V. Yu. Voronkov; E. N. Zolotova; A. I. Skokova (Вестник трансплантологии и искусственных органов)
Introduction. In case of donor heart shortage and expanding pool of patients waiting for heart transplantation (OHTx) liberalization of donor selection, especially use of donors with left ventricular hypertrophy (LVH), may be one of most realistic methods to extending number of OHTx.Aim: to evaluate early and late outcomes after OHTx from donors with LVH ≥1.5 cm.Methods. We reviewed 160 heart recipients who underwent OHTx from donors with LVH 1.5 cm or more from 2011 to 2017.Results. The duration of anesthesia was 6.5 ± 0.7 h, surgery – 4.7 ± 0.3 h, cardiopulmonary bypass – 63–290 (145 ± 47) min and ischemia time was – 86–426 (168 ± 44) min. ICU stay was 7.4 ± 8.5 days. Hospital mortality in the study group was 8,1% (n = 13) and 30-day survival was 91.9%. Patients with or without donor LVH had similar early and long-term survival (p = 0.659).Conclusions. Own experience demonstrates the satisfactory results of HT from donors with LVH. In more cases, LV systolic function of cardiac allograft quickly normalized in the early period after HT.